Homozygous G/G variant of SNP309 in the human MDM2 gene is associated with earlier tumor onset in Caucasian female renal cell carcinoma patients - Stoehr, Christine; Stoehr, R.; Wenners, A.; Hartmann, Arndt; Bertz, Simone; Spath, V.; Walter, B.; Junker, K.; Moch, H.; Hinze, R.; Denzinger, S.; Bond, E. E.; et al. (Oncogenesis, 2016)
Human mouse double minute 2 (Mdm2) plays an essential role in the regulation of the tumor suppressor p53. The G/G variant of SNP309 was shown to increase Mdm2 mRNA/protein expression and to be associated with an increased risk and earlier onset of different cancers in Asian populations. However, the frequency and impact of these G/G variants have not been studied in Caucasian renal cell carcinoma (RCC) patients. Therefore, we analyzed an unselected German cohort of 197 consecutive RCC patients and detected the G/G variant in 18 (9.1%) patients, the G/T variant in 116 (58.9%) patients and the T/T variant in 63 (32.0%) patients. Studying the association between age at tumor onset and SNP309 genotypes, no correlation was detected in the entire RCC cohort or among the male RCC patients. However, the female G/G patients (median age 59.5 years) were diagnosed 13.5 years earlier than the T/T females (median age 73 years). When separating all females into two groups at their median age (68 years), 7 and 1 patients with the G/G variant and 9 and 13 patients with the T/T variant were noted in these age groups (P=0.024). To study the age dependency of tumor onset further, a second, age-selected cohort of 205 RCC patients was investigated, which comprised especially young and old patients. Interestingly, the G/G type occurred more often at lower tumor stages and tumor grades compared with higher stages (P=0.039 and 0.004, respectively). In females, the percentage of the G/G variant was only slightly higher in the younger age group, whereas in males, the percentage of the G/G variant was remarkably higher in the younger age group (19.4% vs 8.0%). In summary, female Caucasian RCC patients with the MDM2 SNP309 G/G genotype showed significantly earlier tumor onset than patients with the wild-type T/T genotype.
EVALuna2:6760